Pengenalan Website Wordwall Sebagai Media Pembelajaran Interaktif di SMP Negeri 3 Tanjung Beringin - Minta Ito Simamora; Yumira Simamora; Sartika Wati; Risna Mira Bella Saragih; Khoiruddin Matondang; Icha Prame Shela (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2025)
Technological developments require teachers to integrate interactive digital media to improve the quality of 21st-century learning. However, early observations at SMP Negeri 3 Tanjung Beringin showed that the utilization of web-based learning media was not optimal despite the availability of supporting facilities. This community service activity aims to introduce the Wordwall platform as an interactive learning media solution and to enhance teachers’ pedagogical competence in operating its features. The implementation method uses a learning-by-doing approach, which includes the preparation stage, workshops through lectures and demonstrations, independent practice in content creation, and evaluation. The results show a significant increase in teachers’ understanding and technical skills in developing digital learning media. Teachers were able to explore quiz features, games, and even printable formats (PDF) to overcome network constraints. In conclusion, this activity successfully narrowed the digital literacy gap and increased teacher motivation to create a more dynamic and student-centered learning environment at SMP Negeri 3 Tanjung Beringin.